2021
DOI: 10.1111/acer.14681
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of reward availability moderate the impact of brief alcohol interventions on alcohol severity in heavy‐drinking young adults

Abstract: Background: Behavioral economic theory predicts that low access to environmental reward is a risk factor for alcohol use disorder (AUD). The Substance-Free Activity Session (SFAS) is a behavioral economic supplement to standard brief alcohol interventions that attempts to increase environmental reward and may therefore have beneficial effects, particularly for individuals with low levels of environmental reward. Methods: Participants were 393 college students who reported at least 2 heavydrinking episodes in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 58 publications
(81 reference statements)
4
13
0
Order By: Relevance
“…A notable and consistent result across these prior studies and the results reported by Murphy et al (2021) is that the frequency of engagement with alternative nonsubstance-related activities and not the ability to experience enjoyment from those activities is what differentiates those with substance use disorders from controls. Also important to note is that the study by Rogers et al (2008) mentioned above was experimental and demonstrated that a contingency-management intervention that reinforced abstinence from cocaine and opiate use increased not only abstinence from drug use but also the frequency of engagement in nonsubstancerelated activities, an observation that also aligns well with the results reported by Murphy et al (2019Murphy et al ( , 2021.…”
Section: Salient Contributi On Ssupporting
confidence: 73%
See 4 more Smart Citations
“…A notable and consistent result across these prior studies and the results reported by Murphy et al (2021) is that the frequency of engagement with alternative nonsubstance-related activities and not the ability to experience enjoyment from those activities is what differentiates those with substance use disorders from controls. Also important to note is that the study by Rogers et al (2008) mentioned above was experimental and demonstrated that a contingency-management intervention that reinforced abstinence from cocaine and opiate use increased not only abstinence from drug use but also the frequency of engagement in nonsubstancerelated activities, an observation that also aligns well with the results reported by Murphy et al (2019Murphy et al ( , 2021.…”
Section: Salient Contributi On Ssupporting
confidence: 73%
“…While only a limited number of studies have examined the PES in relation to substance use, the instrument has nevertheless been demonstrated to be quite effective in characterizing an inverse relationship between engagement in nonsubstance-related activities and drinking and other substance use across multiple populations including college students (Correia et al, 2003), psychiatric patients (Correia & Carey, 1999), outpatients with cocaine use disorder (Van Etten et al, 1998), and outpatients with comorbid cocaine and opioid use disorders (Rogers et al, 2008). A notable and consistent result across these prior studies and the results reported by Murphy et al (2021) is that the frequency of engagement with alternative nonsubstance-related activities and not the ability to experience enjoyment from those activities is what differentiates those with substance use disorders from controls. Also important to note is that the study by Rogers et al (2008) mentioned above was experimental and demonstrated that a contingency-management intervention that reinforced abstinence from cocaine and opiate use increased not only abstinence from drug use but also the frequency of engagement in nonsubstancerelated activities, an observation that also aligns well with the results reported by Murphy et al (2019Murphy et al ( , 2021.…”
Section: Salient Contributi On Ssupporting
confidence: 63%
See 3 more Smart Citations